Nexus of Cash Crop Production Using Improved Varieties and Household Food Security - Eshetie, Aseres Mamo; Matafwali, Eunice; Mwalupaso, Gershom Endelani; Li, Jie; Liu, Aijun (European journal of development research, 2022)
This study evaluates the impact of adopting improved sesame varieties on farm household food security using the data collected in 2018 from potential sesame-growing districts in northwestern Ethiopia. Selectivity and endogeneity probleSms were addressed by endogenous switching regression and the propensity score matching approach. Thus, we estimated the influence of technology adoption on different food security indicators. Our findings indicate that the adoption of new sesame varieties significantly reduced the propensity of food insecurity through increased food consumption expenditures, improved nutritional food intake (consumption scores), and the probability of food security of a household. The finding supports that there is a positive relationship between cash crops and food security. Access to improved sesame seeds, a cash liquidity advantage, extension service efficiency, and farmers’ networking have a significant and positive effect on the adoption of improved sesame varieties. Hence, development policies should be established to motivate cash crop seed multipliers and research institutes to satisfy the seed demand, improve extension service efficiency, and support rural farmers’ primary cooperative. The study enriches the current debate on the subject and provides new empirical evidence of the synergy between cash crops and food security.